2020
DOI: 10.3390/biomedicines8100389
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Traumatic Brain Injury: From Molecular Mechanisms to Therapeutic Interventions

Abstract: Studying the complex molecular mechanisms involved in traumatic brain injury (TBI) is crucial for developing new therapies for TBI. Current treatments for TBI are primarily focused on patient stabilization and symptom mitigation. However, the field lacks defined therapies to prevent cell death, oxidative stress, and inflammatory cascades which lead to chronic pathology. Little can be done to treat the mechanical damage that occurs during the primary insult of a TBI; however, secondary injury mechanisms, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
116
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 391 publications
(437 reference statements)
0
116
1
8
Order By: Relevance
“…Unlike our analysis, effector memory T cells (Tem) populations were up-regulated in TBI (Ritzel et al, 2018 ). Immune responses in TBI are now considered both damaging and beneficial (Jarrahi et al, 2020 ). If regulated, the traumatized brain can benefit from inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our analysis, effector memory T cells (Tem) populations were up-regulated in TBI (Ritzel et al, 2018 ). Immune responses in TBI are now considered both damaging and beneficial (Jarrahi et al, 2020 ). If regulated, the traumatized brain can benefit from inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This resulting ionic imbalance depolarizes the postsynaptic cell membrane, causing a long-lasting increase in excitatory post-synaptic potential. Altered calcium signaling after TBI activates nitric oxide synthase (NOS), proteases, and lipases that trigger cell signaling cascades linked to excitotoxicity and cell death ( Weber, 2012 ; Jarrahi et al, 2020 ). Elevations in nitric oxide (NO) levels interferes with mitochondrial bioenergetics leading to energy depletion, further adding oxidative stress in neurons.…”
Section: Molecular Mechanisms Of Post-traumatic Epilepsymentioning
confidence: 99%
“…Dysfunctional endothelial cell signaling and activation of the immune cell response stimulates the release of proinflammatory mediators, such as ROS, matrix metalloproteinases (MMPs), bradykinins, prostaglandins, cytokines, tachykinins, and excitatory amino acids ( Paudel et al, 2019 ). The formation of intercellular adhesion molecule 1 and vascular cell adhesion protein 1/ERM complex with integrin, via Rac1, releases NADPH oxidase (enzyme involved in oxidative stress) in the endothelial cells generating ROS ( Cerutti and Ridley, 2017 ; Jarrahi et al, 2020 ). Elevations in ROS levels stimulate the release of MMP-2 and 9 causing damage to tight and gap junction proteins such as occludins, claudins and connexin-43.…”
Section: Molecular Mechanisms Of Post-traumatic Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Memantine was not only neuroprotective in animal models of cerebral and spinal cord ischemia but also in models of TBI [23][24][25][26][27][28][29][30][31]. Studies have also shown that blocking NMDAR function with antagonists such as amantadine, improve cognitive outcomes after mild TBI [32,33].…”
mentioning
confidence: 99%